Developing Technology-Based Authentic Assessment for Maharah Kitabah in the Ministry of Religious Affairs' Arabic Textbook - Eka Dewi Mutiara; R. Umi Baroroh; Abdul Aziz Fathullah'ali Abdul Bari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
The Arabic textbook for Grade X MA, published by the Ministry of Religious Affairs in 2020, still requires development in its assessment component to align with the demands of the digital era and 21st-century learning needs. This article aims to analyze and develop a technology-based authentic assessment model for Maharah Kitabah that can be integrated into the Arabic language textbook for grade X MA published by the Ministry of Religious Affairs in 2020. The study employs the type of Research and Development (R&D) with the ADDIE model to the development phase, with a descriptive method to analyze the components of the Maharah Kitabah assessment found in the textbook. The results showed that technology integration in authentic assessment can be done through several platforms: (1) Google Docs for collaborative writing and real-time feedback, (2) Canva for visual presentation development and creative narrative, (3) Augmented Reality for interactive learning, and object-based assessment, (4) Padlet for collaboration and idea sharing, (5) Seesaw for digital portfolios and learning documentation, and (6) Blogger for uploading materials and interacting through the comments column. Each platform has a comprehensive assessment rubric to objectively measure students' writing ability. This development aims to enhance the efficiency of the Maharah Kitabah assessment, foster students' engagement in learning, and better prepare them to meet the demands of the digital era.